1964 AHSME Problems/Problem 8

Revision as of 11:10, 23 July 2019 by Talkinaway (talk | contribs) (Created page with "== Problem== The smaller root of the equation <math>\left(x-\frac{3}{4}\right)\left(x-\frac{3}{4}\right)+\left(x-\frac{3}{4}\right)\left(x-\frac{1}{2}\right) =0</math> is:...")
(diff) ← Older revision | Latest revision (diff) | Newer revision → (diff)

Problem

The smaller root of the equation $\left(x-\frac{3}{4}\right)\left(x-\frac{3}{4}\right)+\left(x-\frac{3}{4}\right)\left(x-\frac{1}{2}\right) =0$ is:

$\textbf{(A)}\ -\frac{3}{4}\qquad \textbf{(B)}\ \frac{1}{2}\qquad \textbf{(C)}\ \frac{5}{8}\qquad \textbf{(D)}\ \frac{3}{4}\qquad \textbf{(E)}\ 1$

Solution

Note that this equation is of the form $a^2 + ab = 0$, which factors to $a(a + b) = 0$. Plugging in $a = x - \frac{3}{4}$ and $b = x - \frac{1}{2}$ gives:

$(x - \frac{3}{4})(x - \frac{3}{4} + x - \frac{1}{2}) = 0$

$(x - \frac{3}{4})(2x - \frac{5}{4}) = 0$

The roots are $x = \frac{3}{4}$ nad $x = \frac{1}{2} \cdot \frac{5}{4}$. The smaller root is $\frac{5}{8}$, which is option $\boxed{\textbf{(C)}}$.

See Also

1964 AHSC (ProblemsAnswer KeyResources)
Preceded by
Problem 7
Followed by
Problem 9
1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40
All AHSME Problems and Solutions

The problems on this page are copyrighted by the Mathematical Association of America's American Mathematics Competitions. AMC logo.png

Invalid username
Login to AoPS